MODEL KEPEMIMPINAN TRANSFORMASIONAL DALAM MENDORONG INOVASI EKONOMI BIRU DI WILAYAH PESISIR (STUDI KASUS KEPULAUAN PANGKEP) - Andi Abdul Razak Ishak; Andi Tenri Lawa Putri Lanrang Haris; Muhammad Taufan Gunawan; Andi Tenri Ellyana Haris; Rahmawati Tahir (STKIP Pesisir Selatan, 2026)
This study aims to analyze the effect of transformational leadership on blue economy innovation in coastal communities of Pangkep Archipelago, Indonesia. A quantitative explanatory approach was employed using a survey method with 100 respondents, including fishermen, aquaculture farmers, seafood processors, marine tourism actors, and community leaders. Data were collected using a Likert-scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Descriptive results revealed that the inspirational motivation dimension obtained the highest score, highlighting positive perceptions of leaders’ ability to motivate and inspire. In contrast, the technological innovation dimension scored relatively low, reflecting limited adoption of environmentally friendly technologies. The outer model assessment confirmed that the measurement indicators met reliability and validity criteria (α > 0.70; CR > 0.70; AVE > 0.50). However, the inner model results indicated that transformational leadership had no significant effect on blue economy innovation (β=0.076; p > 0.05), with an R² value of 0.009. These findings suggest that external factors such as access to capital, technological support, and public policy play a more dominant role in driving innovation in coastal areas.